2022
DOI: 10.1038/s41598-022-12584-9
|View full text |Cite
|
Sign up to set email alerts
|

EF-hand protein, EfhP, specifically binds Ca2+ and mediates Ca2+ regulation of virulence in a human pathogen Pseudomonas aeruginosa

Abstract: Calcium (Ca2+) is well known as a second messenger in eukaryotes, where Ca2+ signaling controls life-sustaining cellular processes. Although bacteria produce the components required for Ca2+ signaling, little is known about the mechanisms of bacterial Ca2+ signaling. Previously, we have identified a putative Ca2+-binding protein EfhP (PA4107) with two canonical EF-hand motifs and reported that EfhP mediates Ca2+ regulation of virulence factors production and infectivity in Pseudomonas aeruginosa, a human patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…2+ . Previously, we have identified and partially characterized Pa Ca 2+ sensor, EfhP (25,49). Here we aimed to characterize the role of this protein in PAO1 transcriptional response to Ca 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2+ . Previously, we have identified and partially characterized Pa Ca 2+ sensor, EfhP (25,49). Here we aimed to characterize the role of this protein in PAO1 transcriptional response to Ca 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified Ca 2+ regulation of numerous Pa virulence factors (33,34,79) contributing to increased mortality in in vivo infection models (35,49,80).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations